Działalność marketingowa polskich uzdrowisk na konkurencyjnym rynku - Lewandowska, Agnieszka (Marketing of the Polish Spa on the Competitive Market, 2005)
The expanded European Union is not only new markets for sale, for the Polish Spa, but it is the large threat from side of competitive other countries. Marketing of Spa is their weakness on European market. The aim of this article is introducing of selected marketing aspects of Polish Spa. This article has been into two parts. The first part refers to essence of marketing of The Polish Spa. The second one presents of solutions which could to increase competitiveness of Polish Spa.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 154-161